Microbiology of Bartholin's Duct Abscess - Anu Mattila; Ari Miettinen; Pentti K. Heinonen (Hindawi Limited, 1994)
Objective: The aim of the study was to determine the currently most frequent microbial findings in Bartholin's duct abscess.